Unilateral renal agenesis in Chilean-Flamingo (Phoenicopterus chilensis) - Ritir Oliveira, Elton Luís [UNESP]; da Costa, André Luiz Mota; Borges, Mariana Fischer [UNESP]; Nemer, Viviane Christiane; Baldissera Gonçalves, Raphael Augusto [UNESP]; Vasconcellos, Matheus [UNESP]; Pacifico Pereira, Keylla Helena Nobre [UNESP]; Schimming, Bruno Cesar [UNESP] (My University, 2020)
Background: Phoenicopterus chilensis is a South American wild bird classified as a near threatened specie in the List of Endangered Species of the International Union for Conservation of Nature. With the increase of the contact between human population and wild animals, this species’ habitat is becoming increasingly vulnerable, with a declining population. Due to the importance of its conservation, the knowledge of abnormalities that affect this species becomes essential. This report aims to describe the first diagnosed case of unilateral renal agenesis in chilean-flamingo. Case: A captive male chilean-flamingo (Phoenicopterus chilensis) was found dead in its enclosure and then was referred at necropsy. The cause of death was the presence of tracheal fungal granuloma, caused by Aspergillus sp. Macroscopically, during the examination of the body cavity, the absence of the right kidney was noted, also evidencing the absence of the caudal renal vein. Emerging from the caudal division of the kidney was noted a blind-end renal vessel. For the histopathological examination, the remaining kidney was fixed in 10% formalin, processed by paraffin embedding technique and stained with Hematoxylin and Eosin (HE). When analyzing the left kidney parenchyma, preserved histological architecture was noted, without any changes in the tissue structures of the organ. Thus, no hypertrophy by compensatory mechanisms of the remaining kidney was observed. Discussion: Unilateral renal agenesis is a very rare congenital defect in dogs, cats and also in birds. It occurs in the complete absence of one of the kidneys, a situation with which the animal can live satisfactorily if there is a normal kidney to assume the functions. In association, ipsilateral ureteral agenesis and compensatory hypertrophy of the remaining kidney may occur. At the time of necropsy, due to the remaining kidney has normal size and within topographic limits, dorsally in contact with the pelvis and sinsacrum, the absence of compensatory hypertrophy was suspected, which was confirmed by histopathological examination. Clinical signs of unilateral renal agenesis, when present, are related to renal failure. The signs develop when the remaining kidney fails to fully absorb the other’s functions and fails to maintain the organism’s homeostasis. In the case of this report, the specimen showed no clinical signs related to renal agenesis, probably because was no functional compensation for the single kidney. This condition was only noticed after flamingo necropsy, who death because tracheal fungal granuloma, caused by Aspergillus sp. Other reported ways of diagnosing this malformation in animals while alive were imaging and abdominal cavity surgery. The etiopathogenesis of unilateral renal agenesis in animals is uncertain, however, the hereditary cause is commonly described in rats and small animals. It cannot be concluded that the same happened with the animal of this study due to the fact of lack of data regarding the parents and history of animal. It is concluded that in unilateral renal agenesis, the compensatory hypertrophy of the remaining kidney and any clinical symptoms may not be present. Necroscopic and complementary exams are essential to obtain the diagnosis of unilateral renal agenesis. Knowing that the chilean-flamingo is considered as a species near threatened of extinction, it is important to know the abnormalities that affect this species, because this information may be essential for conservation programs.
Keywords: Bird; Kidney; Necropsy; Wild animal